Closed-loop systems for plants expressing animal proteins: a modernized framework to safeguard the future of agricultural innovation - Kristin A. Bresnahan; Justin M. Ferber; J. Thomas Carrato; Thomas J. Stoddard; Patrick V. Palad; Magi Richani (Frontiers in Plant Science)
Escalating population growth and climate change pressures on crop production necessitate agricultural innovation to ensure food security and sustainability. Plant molecular farming (PMF), which uses genetically modified (GM) plants to produce high-value proteins for food products, offers a promising solution. PMF products, particularly those that express an animal protein in seed and grain crops, have the potential to substantially benefit U.S. and global agriculture, food systems, economies, and the environment. Farmers can diversify and generate increased revenue streams, while consumers gain access to affordable proteins beyond those currently available. However, the development and commercialization of PMF products, especially those expressing allergenic animal proteins, require careful consideration of existing stewardship guidelines and best practices. Current GM plant stewardship practices must be thoroughly assessed to identify and address any gaps, ensuring that PMF products maintain identity preservation and containment throughout their lifecycle. Implementing a fit-for-purpose closed-loop system (CLS) is crucial for effectively identifying, managing, and mitigating the potential risks and liabilities associated with PMF product development, production, and processing. A CLS framework for PMF products expressing animal proteins should integrate existing best practices from Excellence Through Stewardship and applicable third-party guidelines, including by way of example ISO standards, Good Manufacturing Practices, Hazard Analysis and Risk-Based Preventive Controls, Hazard Analysis and Critical Control Points, and Safe Quality Food, as well as newly designed controls to address potential PMF-specific risks. This comprehensive approach maximizes containment, identity preservation, regulatory compliance, traceability, incident response capabilities, and continuous improvement across the product lifecycle. While customization is required based on each PMF product developer’s specific product and operations, this paper examines industry best practices and describes CLS components that a PMF developer should consider in designing a robust, bespoke CLS to maintain identity preservation and product containment. Such a system will optimize for product quality and integrity while preventing commingling with commodity supplies and any associated market disruption while also addressing food safety. By implementing these rigorous systems, the PMF industry can realize its potential to contribute significantly to sustainable agriculture and food security.